Performance Evaluation Rubric For Philosophy of Education Course Through Ethnodrama Approach - Sani, Paggie Iko Nie; Abdullah, Nurul Hidayah Liew; Ibrahim Mukhtar, Marina (Research and Innovation in Technical and Vocational Education and Training, 2022)
The ethnodrama approach featured in teaching and learning activities gives a new dimension to the Philosophy of Education course. Therefore, the alignment of the evaluation to the ethnodrama approach needs to be parallel in ensuring that the evaluation is made comprehensively. The purpose of this study was to develop a performance evaluation rubric for the Philosophy of Education course through an ethnodrama approach. Rubric development study design using Model for Developing Rubric Scoring Categories Based on Knowledge with qualitative approach. This study involved two FPTV lecturers who had and are teaching the Philosophy of Education course as study participants to obtain the criteria required for the development of a performance appraisal rubric for the ethnodrama approach in the study. Interview sessions using semi-structured interviews then data analysis methods using thematic analysis. Interviews were recorded and written in the form of transcripts of conversations manually. The results show that the domains of cognitive, psychomotor, and affective learning are applied in the Philosophy of Education course. In addition, the domain of performance appraisal that contributed to the development of the rubric was a variety of strategies and methods such as blog writing, radio drama, and virtual drama staging that could promote student learning. The results of the study also developed detailed rubric criteria in performance appraisal through an ethnodrama approach. In conclusion, an appropriate and detailed ethnodrama assessment can result in an effective assessment. The implications of this study can help lecturers evaluate student performance more effectively, consistently, and systematically.